Labour Market Flexibility and Home-leaving in Different Welfare States: Does Labour Force and Contractual Status Matter? - Bertolini, Sonia; Hofäcker, Dirk; Torrioni, Paola (Studies of Transition States and Societies, 2018)
This paper examines the impact of the labour market and the employment status on leaving the parental home in France, Germany and Italy. In particular, temporary employment has concentrated disproportionately among young labour market entrants without safe labour market anchorage. One consequence for young adults remaining in unemployment or non-permanent jobs is the postponement of important decisions in their private lives such as home-leaving; whereas the length of postponement depends on the institutional context. Less attention has been paid to the analysis of education-specific patterns in the effects of employment precariousness on individual decision-making. The paper aims to fill this gap by analysing whether and how the employment status (employed/unemployed) as well as the type of contract (fixed-term/permanent) influences the first transition of leaving the parental home, and how this effect varies according to the level of education in three different institutional contexts. To this end, the paper uses a mixed method approach, combining results from a quantitative analysis of data from the European Labour Force Survey 2010 with findings from qualitative research based on interviews and focus groups with people aged 20-45 to highlight the mechanism driving young peoples’ decisions.